What are the Factors that Determine the Number of People Coming to China? (Journal of Nonlinear Modeling and Analysis, 2024)
This paper studies the factors that affect people coming to China.We select the spending of United States and South Korea, GDP, railway transportation capacity of China as observations. Based on the data from 1988 to2015, we use the ordinary least squares analysis regression model and present amost reasonable regression equation. It is found that South Korea's spendingis negative to the number of visitors, whereas the spending of US is positive.On comparing the effect of other variables, the growth of railway transportation capacity and the overseas travel expenses of South Korea or United States,have almost no significant impact on the number of people coming to China.However, as China economic growth increasing rapidly, more and more peopleare willing to come.
Keywords: Least squares analysis; regression; correlation coefficient.